1987
DOI: 10.1111/j.2042-7158.1987.tb03157.x
|View full text |Cite
|
Sign up to set email alerts
|

The calcium channel antagonist, verapamil, potentiates the inhibitory action of morphine on intestinal and biliary motility

Abstract: The effects of morphine and verapamil have been assessed on the gastrointestinal propulsion of charcoal meal and egg yolk-induced gall bladder emptying in mice. Each drug significantly inhibited these functions. In combination, an additive effect was seen on the inhibition of gastrointestinal transit, whilst verapamil potentiated the morphine-induced inhibition of gall bladder emptying. It is concluded that calcium ion channel antagonists may potentiate the activity of opiate drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The finding that verapamil did not suppress the basal gastrointestinal transit (see Figure 4) is in agreement with the work by di carlo et al . (1993) , while some other studies have revealed decreased gastrointestinal transit following verapamil ( Shah et al ., 1987 ; Calignano et al ., 1992 ). The effectiveness of verapamil in the resting state might vary with experimental conditions such as the strain or size of mice employed.…”
Section: Discussionmentioning
confidence: 92%
“…The finding that verapamil did not suppress the basal gastrointestinal transit (see Figure 4) is in agreement with the work by di carlo et al . (1993) , while some other studies have revealed decreased gastrointestinal transit following verapamil ( Shah et al ., 1987 ; Calignano et al ., 1992 ). The effectiveness of verapamil in the resting state might vary with experimental conditions such as the strain or size of mice employed.…”
Section: Discussionmentioning
confidence: 92%
“…To d o this we studied the effects of clonidine, an az-adrenoceptor agonist which is known to antagonize some withdrawal symptoms in animals and man, and nifedipine, a calcium channel antagonist. There is evidence that calcium plays a role in the antinociceptive action of opiates as well as in the development of tolerance and physical dependence (Harris et al 1976;Bongianni et al 1986;Shah et al 1987a) and binding sites for calcium blocking drugs have been found in intestinal smooth muscles (Bolger et al 1983).…”
mentioning
confidence: 97%
“…There is evidence that calcium plays a role in the antinociceptive action of opiates as well as in the development of Correspondence to: P. Valeri, Institute of Pharmacology and Phamacognosy, University of Rome "La Sapienza", 001 85 Rome, Italy. tolerance and physical dependence (Harris et al 1976;Bongianni et al 1986;Shah et al 1987a) and binding sites for calcium blocking drugs have been found in intestinal smooth muscles (Bolger et al 1983).…”
mentioning
confidence: 99%
“…Apigenin, quercetin and other flavonoids inhibit enzymes involved in arachidonate metabolism (Mascolo et al, 1988). However, the (Abdalla and Abu Zarga, 1987;Shah et al, 1987;Meli et al, 1990). Flavonoids are useful in relieving gastrointestinal colic, diarrhoea and/or other gastrointestinal disorders.…”
mentioning
confidence: 98%